Keefektifan Pembelajaran Proyek Sains terhadap Kemampuan Pemecahan Masalah dan Sosial Emosional di TK Kenanga Kelompok B - Masatun, Masatun; Chandra, Anita; Sumarno, Sumarno (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The inability of group B children at Kenanga Kindergarten to solve problems and it is known that their social and emotional abilities are still low is the problem of this research. This research aims to determine the effectiveness of science project-based learning on the problem-solving and socio-emotional abilities of children aged 5-6 years at Kenanga Kindergarten, Karanganyar Village. The research approach is quantitative with a quasi-experimental type. The research sample consisted of 30 people and was divided into two sample classes (experimental samples and control samples). The research results show that the results of the t test for problem solving ability show a value of Sig. (2-tiled) 0.001 < 0.005, which means there is a significant difference in the average value of the pretest and posttest problem solving ability variables. The N-Gain Score test is 78.23%, meaning that science project learning is effective in improving children's problem solving abilities. Meanwhile, the results of the social ability t test show the significance value of the t test Sig. (2-tiled) 0.015 < 0.05, meaning there is a significant difference in the average pre-test and post-test scores for science project learning on children's social-emotional abilities. The n-gain score test results were 76.48%, this means that science project learning is effective in improving children's social emotional abilities.